Choice of alternative dispute resolutions in construction disputes - Abd. Halim, Fazzarieyyah (2014)
The adversarial natures of Construction Industry contribute construction disputes. This research aim to study Alternative Dispute Resolutions (ADRs) process and to propose the preferred ADRs that can minimise the time, cost and to preserve reputation and to propose enhancement criteria in current ADRs. Literature review was carried out and questionnaire was formulated and distributed to project participants in Johor Bahru. The data collected was analysed using Relative Important Index (RII). The analysis proved that from the null hypotheses variables tested, Negotiation matched 69% of the preferred resolution in the industry with some enhancement needed on this technique. The relationship and reputations rank the highest preference criteria with cost and duration fall on rank 10 and 11 respectively. Negotiation remains the most significant resolution method of construction disputes.